Deep eutectic solvent enhances antibacterial activity of a modular lytic enzyme against Acinetobacter baumannii - Aleksandra Maria Kocot; Tomasz Swebocki; Karolina Ciemińska; Adrianna Łupkowska; Małgorzata Kapusta; Dennis Grimon; Ewa Laskowska; Anna-Karina Kaczorowska; Tadeusz Kaczorowski; Rabah Boukherroub; Yves Briers; Magdalena Plotka (Scientific Reports)
Abstract In this study, we evaluated the combined effect between MLE-15, a modular lytic enzyme composed of four building blocks, and reline, a natural deep eutectic solvent. The bioinformatic analysis allowed us to determine the spatial architecture of MLE-15, whose components were bactericidal peptide cecropin A connected via a flexible linker to the cell wall binding domain (CBD) of mesophilic 201ϕ2 − 1 endolysin and catalytic domain (EAD) of highly thermostable Ph2119 endolysin. The modular enzyme showed high thermostability with the melting temperature of 93.97 ± 0.38 °C, significantly higher than their natural counterparts derived from mesophilic sources. The minimum inhibitory concentration (MIC) of MLE-15 was 100 µg/mL for a panel of Gram-positive and Gram-negative bacteria, while the MIC of reline ranged from 6.25 to 25% v/v for the same strains. The addition of reline effectively reduced the MIC of MLE-15 from 100 µg/mL to 3.15–50 µg/mL. This combination displayed additive effects for most strains and synergism for extensively antibiotic-resistant Acinetobacter baumannii and Bacillus subtilis. The subsequent evaluation revealed that MLE-15 eliminated planktonic cells of A. baumannii RUH134, but was ineffective against matured biofilms. However, combined with reline, MLE-15 reduced the bacterial load in the matured biofilm by 1.39 log units. Confocal fluorescence microscopy indicated that reline damaged the structure of the biofilm, allowing MLE-15 to penetrate it. Additionally, MLE-15 and its combination with reline eradicated meropenem-persistent cells of A. baumannii RUH134. Effectiveness in lowering the MIC value of MLE-15 as well as protection against antibiotic-tolerant persister cells, indicate that MLE-15 and reline combination is a promising candidate for effective therapies in bacterial infections, which is especially important in the light of the global crisis of antimicrobial resistance.